Regenerative medicine for spinal cord injury: focus on stem cells and biomaterials. (2nd October 2020) - Papa, Simonetta; Pizzetti, Fabio; Perale, Giuseppe; Veglianese, Pietro; Rossi, Filippo
ABSTRACT: Introduction: Spinal cord injury (SCI) is a dramatic medical pathology consequence of a trauma (primary injury). However, most of the post-traumatic degeneration of the tissue is caused by the so-called secondary injury, which is known to be a multifactorial process. This, indeed, includes a wide spectrum of events: blood-brain barrier dysfunction, local inflammation, neuronal death, demyelination and disconnection of nerve pathways. Areas covered: Cell therapy represents a promising cure to target diseases and disorders at the cellular level, by restoring cell population or using cells as carriers of therapeutic cargo. In particular, regenerative medicine with stem cells represents the most appealing category to be used, thanks to their peculiar features. Expert opinion: Many preclinical research studies demonstrated that cell treatment can improve animal sensory/motor functions and so demonstrated to be very promising for clinical trials. In particular, recent advances have led to the development of biomaterials aiming to promote in situ cell delivery. This review digs into this topic discussing the possibility of cell treatment to improve medical chances in SCI repair.